Increased baseline occupancy of D(2) receptors by dopamine in schizophrenia - Abi-Dargham, Anissa (The National Academy of Sciences, 2000)
The classical dopamine hypothesis of schizophrenia postulates a hyperactivity of dopaminergic transmission at the D(2) receptor. We measured in vivo occupancy of striatal D(2) receptors by dopamine in 18 untreated patients with schizophrenia and 18 matched controls, by comparing D(2) receptor availability before and during pharmacologically induced acute dopamine depletion. Acute depletion of intrasynaptic dopamine resulted in a larger increase in D(2) receptor availability in patients with schizophrenia (19% ± 11%) compared with control subjects (9% ± 7%, P = 0.003). The increased occupancy of D(2) receptors by dopamine occurred both in first-episode neuroleptic-naive patients and in previously treated chronic patients experiencing an episode of illness exacerbation. In addition, elevated synaptic dopamine was predictive of good treatment response of positive symptoms to antipsychotic drugs. This finding provides direct evidence of increased stimulation of D(2) receptors by dopamine in schizophrenia, consistent with increased phasic activity of dopaminergic neurons.